Exciton localization and structural disorder of GaAs1−xBix/GaAs quantum wells grown by molecular beam epitaxy on (311)B GaAs substrates. (17th July 2018) - Prando, G A; Orsi Gordo, V; Puustinen, J; Hilska, J; Alghamdi, H M; Som, G; Gunes, M; Akyol, M; Souto, S; Rodrigues, A D; Galeti, H V A; Henini, M; et al.
Abstract: In this work, we have investigated the structural and optical properties of GaAs(1−x) Bix /GaAs single quantum wells (QWs) grown by molecular beam epitaxy on GaAs (311)B substrates using x-ray diffraction, atomic force microscopy, Fourier-transform Raman (FT-Raman) and photoluminescence spectroscopy techniques. The FT-Raman results revealed a decrease of the relative intensity ratio of transverse and longitudinal optical modes with the increase of Bi concentration, which indicates a reduction of the structural disorder with increasing Bi incorporation. In addition, the PL results show an enhancement of the optical efficiency of the structures as the Bi concentration is increased due to important effects of exciton localization related to Bi defects, nonradiative centers and alloy disorder. These results provide evidence that Bi is incorporated effectively into the QW region. Finally, the temperature dependence of the PL spectra has evidenced two distinct types of defects related to the Bi incorporation, namely Bi clusters and pairs, and alloy disorder and potential fluctuation.